The question that I'm stuck on reads as follows:

The substitution rule can sometimes be used to simplify the evaluation of an integral of an even or odd function. What can you say about the integral $\int\limits_{-a}^a{f(x)dx}$ if

a) $f$ is an even function

b) $f$ is an odd function

Give reasons for your answers.

I ignored the part about the substitution rule, and tried to prove for a) that $\int\limits_{-a}^a{f(x)dx}=2F(a)$ (which I assumed using common sense). However, my solution for a) consistently came out as 0. For example,

$\int\limits_{-a}^a{f(x)dx}=\int\limits_{-a}^0{f(x)dx}+\int\limits_{0}^a{f(x)dx}\\ =F(0)-F(-a)+F(a)-F(0)=-F(a)+F(a)=0$

$\ $

So, I then tried a Riemann sum: $\displaystyle\lim_{n \to \infty}\left[\frac{0-(-a)}{n}\sum_{i=0}^{n}{f\left(-a+\frac{0-(-a)i}{n}\right)}\right]+\displaystyle\lim_{n \to \infty}\left[\frac{a}{n}\sum_{i=0}^{n}{f\left(\frac{ai}{n}\right)}\right]\\ =\displaystyle\lim_{n \to \infty}\left[\frac{a}{n}\left(f(-a)+f\left(-a+\frac{a}{n}\right)+f\left(-a+\frac{2a}{n}\right)+...+f(-a+a)\right)\right]+\displaystyle\lim_{n \to \infty}\left[\frac{a}{n}\left(f(0)+f\left(\frac{a}{n}\right)+...+f\left(\frac{a(n-1)}{n}\right)+f(a)\right)\right]\\ =\displaystyle\lim_{n \to \infty}\left[\frac{a}{n}\left(f(0)-f(0)+f\left(\frac{a}{n}\right)-f\left(\frac{a}{n}\right)+...+f\left(a-\frac{a}{n}\right)-f\left(a-\frac{a}{n}\right)+f(a)-f(a)\right)\right]\\ =0$

$\ $

What am I doing wrong?

  • $\begingroup$ Well for one thing, your LaTeX is all messed up! $\endgroup$ – M. Vinay Jun 9 '14 at 8:02
  • $\begingroup$ Ugh!? Your post hurts my eyes. $\endgroup$ – Tunk-Fey Jun 9 '14 at 8:03
  • $\begingroup$ Sorry. It's my first time on this site. Does [tex] [/tex] not work? I don't know how to do previews either. $\endgroup$ – ahorn Jun 9 '14 at 8:04
  • $\begingroup$ @user151595 No, just replace all the [tex] and [/tex] by $'s. $\endgroup$ – M. Vinay Jun 9 '14 at 8:05
  • $\begingroup$ The second-last equality is incorrect. $\endgroup$ – ahorn May 12 '16 at 20:21

The statement $$\int\limits_{-a}^a{f(x)dx}=\int\limits_{-a}^0{f(x)dx}=\int\limits_{0}^a{f(x)dx}\\ =F(0)-F(-a)+F(a)-F(0)=-F(a)+F(a)=0$$ is false because it is the integrand $f(x)$ that is even, not its antiderivative $F(x)$. That is to say, $f(x) = f(-x)$ for all $x \in \mathbb R$ does not imply that $F(x) = F(-x)$ where $F$ is a function that satisfies $F'(x) = f(x)$. Rather, you should write with the substitution $u = -x$, $du = -dx$, $$\int_{x=-a}^0 f(x) \, dx = \int_{u=a}^0 f(-u) \, (-du) = \int_{u=0}^a f(-u) \, du = \int_{u=0}^a f(u) \, du,$$ and the only place where we use the evenness of $f$ is in the rightmost equality above.

  • $\begingroup$ I don't understand why $f(x)=f(−x)$ for all $x \in \mathbb R$ does not imply that $F(x)=F(−x)$ where $F$ is the anti-derivative of $f$. If I draw a graph of $f(x)=x^2$, the area will be the same on either side of the origin. I used your method on the integral $\int\limits_0^a{f(x)dx}$ and got $\int\limits_{-a}^0{f(u)du}$, so I added them to get $\int\limits_{-a}^a{f(u)du}=\int\limits_{a}^{-a}{f(x)dx}$. Do you think that is the answer they are looking for? I also used the same method on b), and got the same answer of $\int\limits_{a}^{-a}{f(x)dx}$. $\endgroup$ – ahorn Jun 9 '14 at 11:27
  • 1
    $\begingroup$ For example: $f(x) = 1$ satisfies $f(x)=f(-x)$, but the antiderivative $F(x) = x$ does not satisfy $F(x)=F(-x)$. $\endgroup$ – GEdgar Jun 9 '14 at 12:32
  • $\begingroup$ The second equals sign should be a $+$. I recommended an edit two years ago, but it was incorrectly rejected. $\endgroup$ – ahorn May 12 '16 at 20:06

There was a mistake across the second-last equality of my Riemann sum:

$=\displaystyle\lim_{n \to \infty}\left[\frac{a}{n}\left(f(-a)+f\left(-a+\frac{a}{n}\right)+f\left(-a+\frac{2a}{n}\right)+...+f(-a+a)\right)\right]+\displaystyle\lim_{n \to \infty}\left[\frac{a}{n}\left(f(0)+f\left(\frac{a}{n}\right)+...+f\left(\frac{a(n-1)}{n}\right)+f(a)\right)\right]\\ =\displaystyle\lim_{n \to \infty}\left[\frac{a}{n}\left(f(0)+f(0)+f\left(\frac{a}{n}\right)+f\left(\frac{a}{n}\right)+...+f\left(a-\frac{a}{n}\right)+f\left(a-\frac{a}{n}\right)+f(a)+f(a)\right)\right]\\ =2\displaystyle\int_0^a f(x) dx$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.